Community-Based Halal Tourism on Lombok Island: Analysis of the Relationship Between Community Participation, Compliance with Halal Standards, Local Economic Benefits, and Cultural Environmental Preservation - Reza Arviciena Sakti; Abdul Basit; Oliver William Knight; Yudhi Kurniawan Zahari (Indonesian Journal of Islamic Economics and Business, 2026)
This study aims to analyze the relationship between community participation, halal standards compliance, local economic benefits, and cultural–environmental preservation in the development of community-based halal tourism on Lombok Island. Halal tourism development is expected not only to increase tourist visits but also to generate economic benefits for local communities while supporting cultural and environmental sustainability. This research uses a quantitative explanatory approach, with data collected through Likert-scale questionnaires, observation, and documentation from communities involved in halal tourism using purposive sampling. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach through SmartPLS. The results show that community participation and halal standards compliance significantly influence local economic benefits, while local economic benefits positively affect cultural and environmental preservation. Additionally, community participation and halal standards compliance also directly contribute to cultural and environmental sustainability in halal tourism destinations. Therefore, strengthening collaboration among communities, government, and tourism stakeholders is essential to ensure that halal tourism development supports sustainable economic, cultural, and environmental outcomes